The Significance of Planned Fertility Preservation for Women With Endometrioma Before an Expected Ovarian Cystectomy - Hong, Yeon Hee; Lee, Hyun Kyoung; Kim, Seul Ki; Lee, Jung Ryeol; Suh, Chang Suk (Frontiers in Endocrinology, 2021)
Endometrioma is known to reduce the ovarian reserve and the extent of the decrease is more severe when ovarian surgery is performed. Therefore, to prevent this decline in fertility, patients with endometrioma are considered candidates for preoperative fertility preservation (FP). In this study, we evaluate the efficacy of FP in women with endometrioma before planned ovarian surgery. A total of 95 cycles in 62 patients with endometrioma, undergoing controlled ovarian stimulation (COS) for FP using a gonadotropin-releasing hormone (GnRH) antagonist protocol before an expected ovarian surgery, were enrolled retrospectively. COS outcomes were compared according to endometrioma laterality. Additionally, first COS cycle outcomes in patients with endometrioma were compared with those in infertile patients, or in patients with a benign ovarian cyst using propensity score matching. When multiple COS cycles were performed, the results of cumulative cycles were analyzed. Embryo quality was worse in the bilateral endometrioma group. Compared with the infertile patient group, the patients with endometrioma had significantly lower Anti-Müllerian Hormone (AMH) and fewer numbers of oocytes retrieved (median, 3.3 vs. 1.2, p<0.001; 7.0 vs. 4.0, p=0.009, respectively). Compared with mature oocytes in infertile patients or patients with a benign cyst, mature oocytes were fewer in patients with endometrioma, but this was not statistically significant (median, 4.0 vs. 3.0, p=0.085; 5.5 vs. 3.0, p=0.052, respectively). The median value of the cumulative number of cryopreserved oocytes or embryos was 14.5 up to the fourth cycle compared to 3 up to the first cycle, with cumulative effect. Women with endometrioma should be counseled for FP before planned ovarian cystectomy. The number of cryopreserved oocytes or embryos can be increased by repeated cycles.